Management for Paddy, Oil Palm, and Pineapple Plantations in Malaysia: Current Status and Reviews - Sahil Mohedin Hawa; Hillry Gibson Anak Panjang; Ericson Nyagang; Wan Sieng Yeo; Agus Saptoro; Shiew Wei Lau Lau; Tze Khiun Jong; Alex Choon Teck Jong (Journal of Applied Science & Process Engineering, 2021)
Heavy rainfall causes a loss of fertiliser to the environment, and it leads to environmental issues such as eutrophication. Replenishment of fertiliser to replace the loss imposes a financial impact since frequent applications are costly and labour intensive. Therefore, investigations on proper fertiliser application in maintaining good soil pH, improving plant growth, and increasing crop yield from various plantations across Malaysia are of paramount importance. Meanwhile, limited agricultural-related studies about crop management in Malaysia have been done. This study presents a state-of-the-art review of Malaysia’s paddy, oil palm, pineapple plantations, and the existing nutrient management and fertilisation practices throughout the crop cycle. A systematic study of the existing crop management in terms of farming practices, nutrient management, and fertiliser application on the plantations of paddy, oil palm, and pineapple in Malaysia was carried out. Industry overviews for these three crop types based on past situations and future directions are also included. Recommendations on how to better manage these plantations are also outlined to promote a better understanding of the past, current, and future direction of the agricultural activities and management for principal edible crops like paddy, oil palm, and pineapple in Malaysia.